Effectiveness of Vaccination Against Tick-Borne Encephalitis in the Czech Republic, 2018-2022 - Kyncl, Jan; Angulo, Frederick J; Orlikova, Hana; Zhang, Pingping; Vlckova, Iva; Maly, Marek; Krivohlavkova, Dagmar; Harper, Lisa R; Edwards, Juanita; Bender, Cody; Pilz, Andreas; Erber, Wilhelm; et al. (Vector borne and zoonotic diseases (Larchmont, N.Y.), 2024)
Background: Tick-borne encephalitis (TBE) is caused by the tick-borne encephalitis virus (TBEV). TBEV infection can cause symptoms of central nervous system (CNS) inflammation and result in severe consequences including death. TBE is an increasing health threat in the Czech Republic and elsewhere in Europe. In 2020, 23% of 3734 TBE cases reported to the European Centre for Disease Prevention and Control were from the Czech Republic. TBE vaccination is universally recommended in the Czech Republic, but a full analysis of TBE vaccine effectiveness (VE) in the Czech Republic has not been published. Methods: TBE is a notifiable disease in the Czech Republic with mandatory reporting of cases (i.e., laboratory-confirmed TBEV infected patient with symptoms of CNS inflammation) and vaccination history to public health authorities. TBE VE was estimated using the screening method utilizing public health surveillance data from 2018 to 2022 and online household surveys of the general population on TBE vaccine uptake conducted in 2019-2022. Results: In 2018-2022, 3648 TBE cases were reported in the Czech Republic; 98.1% (3105/3166) of TBE cases with known vaccination history were unvaccinated. Among 42,671 persons surveyed from the general population who had known TBE vaccination history, 66.5% were unvaccinated. VE against TBE was 97.6% (95% confidence interval 95.7-98.7). When stratified by age group, VE was 97.1% (88.4-99.3) in 1-15 years of age, 97.9% (95.3-99.0) in 16-59 years of age, and 96.9% (90.5-99.0) in ≥60 years of age. TBE vaccination averted an estimated 1020 TBE cases in the Czech Republic from 2018 to 2022. Conclusions: This first published study with a full analysis of TBE VE in the Czech Republic showed that vaccination was highly effective for the prevention of TBE including in children, an age group with increasing TBE disease burden. Vaccination averted hundreds of TBE cases and hospitalizations despite the relatively low compliance with TBE vaccine recommendations. To prevent additional TBE cases in the Czech Republic, enhanced efforts to increase TBE vaccine uptake are needed.
Keywords: dospělí; vector-borne disease; surveillance; Female; Infant; dítě; předškolní dítě; Viral Vaccines; Adult; ženské pohlaví; mladý dospělý; vakcinace; Adolescent; lidé; virové vakcíny; viry klíšťové encefalitidy; Encephalitis Viruses, Tick-Borne; epidemiology; Vaccination; Male; kojenec; Czech Republic; Aged; Young Adult; Child, Preschool; Encephalitis, Tick-Borne; Česká republika; lidé středního věku; Child; senioři; mužské pohlaví; klíšťová encefalitida; Middle Aged; mladiství; prevention; Humans